Pattern of New Gene Origination in a Special Fish Lineage, the Flatfishes - Haorong Li (MDPI AG, 2021)
Origination of new genes are of inherent interest of evolutionary geneticists for decades, but few studies have addressed the general pattern in a fish lineage. Using our recent released whole genome data of flatfishes, which evolved one of the most specialized body plans in vertebrates, we identified 1541 (6.9% of the starry flounder genes) flatfish-lineage-specific genes. The origination pattern of these flatfish new genes is largely similar to those observed in other vertebrates, as shown by the proportion of DNA-mediated duplication (1317; 85.5%), RNA-mediated duplication (retrogenes; 96; 6.2%), and de novo–origination (128; 8.3%). The emergence rate of species-specific genes is 32.1 per Mya and the whole average level rate for the flatfish-lineage-specific genes is 20.9 per Mya. A large proportion (31.4%) of these new genes have been subjected to selection, in contrast to the 4.0% in primates, while the old genes remain quite similar (66.4% vs. 65.0%). In addition, most of these new genes (70.8%) are found to be expressed, indicating their functionality. This study not only presents one example of systematic new gene identification in a teleost taxon based on comprehensive phylogenomic data, but also shows that new genes may play roles in body planning.